Evaluation of genes associated with human myxomatous mitral valve disease in dogs with familial myxomatous mitral valve degeneration. (February 2018) - Meurs, K.M.; Friedenberg, S.G.; Williams, B.; Keene, B.W.; Atkins, C.E.; Adin, D.; Aona, B.; DeFrancesco, T.; Tou, S.; Mackay, T.
Highlights: We hypothesized that a mutation associated with human mitral valve disease (MMVD) is associated with canine disease. Sequenced DNA of MMVD Cavalier King Charles spaniels (CKCS) and Dachshunds and evaluated genes associated with human MMVD. No variant predicted to be of functional significance was identified in any gene of interest. Mitral valve disease in the CKCS and Dachshund may not share an identical genetic cause with the human MMVD. Abstract: Myxomatous mitral valve disease (MMVD) is the most common heart disease in the dog. It is believed to be heritable in Cavalier King Charles spaniels (CKCS) and Dachshunds. Myxomatous mitral valve disease is a familial disease in human beings as well and genetic mutations have been associated with its development. We hypothesized that a genetic mutation associated with the development of the human form of MMVD was associated with the development of canine MMVD. DNA was isolated from blood samples from 10 CKCS and 10 Dachshunds diagnosed with MMVD, and whole genome sequences from each animal were obtained. Variant calling from whole genome sequencing data was performed using a standardized bioinformatics pipeline for all samples. After filtering, the canine genes orthologous to the human genes known to be associated with MMVD were identified and variants were assessed for likely pathogenic implications. No variant was found in any of the genes evaluated that was present in least eight of 10 affected CKCS or Dachshunds. Although mitral valve disease in the CKCS and Dachshund is a familial disease, we did not identify genetic cause in the genes responsible for the human disease in the dogs studied here.